Antioxidant capacity of trans-resveratrol dietary supplements alone or combined with the mycotoxin beauvericin. (July 2017) - Mallebrera, Beatriz; Maietti, Annalisa; Tedeschi, Paola; Font, Guillermina; Ruiz, Maria-Jose; Brandolini, Vincenzo
Abstract: Trans -resveratrol ( trans -RSV) is a polyphenol with multiples biological properties, such as anti-inflammatory, antioxidant, anti-aging, anti-diabetic, and antiplatelet. It occurs naturally in grapes and derivate, peanuts and berries. Beauvericin (BEA) is a mycotoxin present in cereals that produces cytotoxicity, intracellular reactive oxygen species and lipid peroxidation. The general objective of this research was to evaluate whether trans -RSV could be used as a good polyphenol against damages produced by BEA. Because trans -RSV can be ingested through dietary supplements, to reach this goal, the following specific objectives were proposed: to determine a) the trans -RSV content in different polyphenol dietary supplements by capillary electrophoresis, b) the antioxidant capacity of the trans -RSV in polyphenol supplements, and c) the influence of BEA in the antioxidant capacity of trans -RSV when they are in combination by photochemioluminiscence assay. The results obtained in this study showed that all polyphenol dietary supplements present higher RSV content that the content of the label. The polyphenol supplements present antioxidant capacity. And the combination of trans -RSV and BEA did not affect the antioxidant capacity of trans -RSV. Thus, RSV could contribute to decrease oxidant effects produced by BEA.